Evaluation Of Soil Bearing Capacity Based On Cone Penetration Test (CPT) Results In Gunungsitoli City, Indonesia - Bimawijaya Laia; Jefri Rahmat Daeli; Andrew Christover Harefa; Piter Telaumbanua; Kevin Berkat Mendrofa (CV. SINAR HOWUHOWU, 2026)
Soil bearing capacity is a critical parameter in geotechnical engineering that determines the safety, stability, and performance of foundation systems. Accurate evaluation of bearing capacity is essential for selecting appropriate foundation types and preventing excessive settlement or structural failure. This study aims to evaluate the soil bearing capacity in Gunungsitoli City, Indonesia, based on Cone Penetration Test (CPT) results. A quantitative descriptive research approach was employed using in-situ CPT data collected from six representative investigation points. The analysis involved the interpretation of cone tip resistance (qc), sleeve friction (fs), friction ratio (Rf), soil stratification, and estimation of allowable bearing capacity through established empirical correlations. The results indicate that cone resistance generally increases with depth, reflecting a transition from soft clay and silty sand near the ground surface to dense sandy deposits at greater depths. The estimated allowable bearing capacity ranges from 320 kPa to 500 kPa, depending on local subsurface conditions. These values suggest that isolated footings are suitable for light to medium-rise structures, whereas raft or pile foundations are recommended for heavier infrastructure. Spatial variations in bearing capacity demonstrate the influence of local geological conditions, emphasizing the necessity of conducting site-specific geotechnical investigations before construction. Overall, the study confirms that the Cone Penetration Test provides a reliable, efficient, and economical method for evaluating soil bearing capacity and supports safer and more cost-effective foundation design for future infrastructure development in Gunungsitoli City.